DNA strand breaks at centromeres: friend or foe? - Graham, E; Esashi, F (Elsevier, 2023)
Centromeres are large structural regions in the genomic DNA, which are essential for accurately transmitting a complete set of chromosomes to daughter cells during cell division. In humans, centromeres consist of highly repetitive α-satellite DNA sequences and unique epigenetic components, forming large proteinaceous structures required for chromosome segregation. Despite their biological importance, there is a growing body of evidence for centromere breakage across the cell cycle, including periods of quiescence. In this review, we provide an up-to-date examination of the distinct centromere environments at different stages of the cell cycle, highlighting their plausible contribution to centromere breakage. Additionally, we explore the implications of these breaks on centromere function, both in terms of negative consequences and potential positive effects.